UPAYA MENINGKATKAN PROFESIONALITAS GURU BAHASA INDONESIA DI SMPN 3 NIBUNG HANGUS - Mariam, Siti (Faculty of Tarbiyah nad Teacher Training, 2023)
This research examines efforts to improve the professionalism of Indonesian language teachers at SMPN 3 Nibung Hangus. This research uses a descriptive qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The data analysis techniques used in this research are data collection, data reduction and drawing conclusions. The research results show that: 1) Strategies that can be used to develop teachers' professional competence in carrying out their duties, namely through the In Service Training program; (2) The principal's leadership strategy in developing the professional competence of teachers at SMPN 3 Nibung Hangus includes two strategies, the first is the formal strategy, namely the teacher is directed by the institution to take part in education and training, the second strategy, namely the non-formal teacher with a strong desire and motivation must be able to train and develop potential related to the teaching profession. Furthermore, there are several obstacles in teacher professional development, namely (a) Lack of teacher interest independently in creating new creativity and innovation in learning because teachers lack mastery of learning models, methods and strategies; (b) Some teachers have non-teaching educational backgrounds so their ability to understand psychology and pedagogy is still relatively low; and (c) Inadequate facilities and infrastructure.